Cognitive Interview-Based Validation of the UK Forensic Quality of Life Questionnaire – Short Version (UKFQL-SV). Issue 3 (27th May 2023) - Simler, Amber; Hartwright, Christopher; Lawrence, Daniel; Davies, Bronwen
ABSTRACT: Quality of life for people who use forensic mental health services has been the topic of increased empirical and clinical interest in recent years. Despite this, no well-validated quality of life measure exists for use with this specific clinical population in the UK. The Forensic Quality of Life Questionnaire – Short Version (FQL-SV) is a psychometrically valid quality of life measure developed in the Netherlands and translated into English. The current study aimed to explore the validity of the English version of the FQL-SV (EFQL-SV) using a think aloud and concurrent probing cognitive interviewing procedure. Fifteen service users participated from UK-based forensic mental health services. Comprehension of the EFQL-SV was evaluated systematically. and findings indicated that the most significant difficulty for participants was the understanding of the wording of EFQL-SV items. This meant that the EFQL-SV was limited in the extent to which it measured what it purports to. A number of revisions to the EFQL-SV have been proposed but require further validation. We have titled the adapted measure the UK Forensic Quality of Life – Short Version.